THE EFFECT OF STUDENT TEAM ACHIEVEMENT DIVISION (STAD) TECHNIQUE ON STUDENTS’ SPEAKING SKILLS OF GRADE XII STUDENTS OF SMA N.1 BRANDAN BARAT - Edi Suprayetno; Fernando De Napoli Marpaung; Yusrah Yusrah (Institut Pendidikan Tapanuli Selatan, 2022)
This study aimed to investigate the effect of the Student Team Achievement Divisions (STAD) Technique on the speaking skill of Grade XII Students of SMA N. 1 Brandan Barat and the students’ perceptions toward the implementation of the STAD technique in teaching speaking. An experimental design with instruments of tests and questionnaires to collect the data was applied in this study. A random sampling technique of 60 students of grade XII of SMA N.1 Brandan Barat academic year 2021/2022 was taken as two sample classes. One class of 30 students was an experimental group (XII IPS1) and another one of 30 students was appointed as a control group (XII IPS2). The STAD technique was applied in the experimental group while the conventional method was applied in the control group. From the data analysis, it was found that the STAD technique positively affected the students' speaking skills with the Tcount score 3,443 was greater than the ttable score 2,048 (3,443 > 2,048) with a significance level of sig 0,001 < 0.05. (5 percent) then it can be argued that Ho was rejected and Ha was accepted or It can be concluded that the STAD technique affected a better student's performance in speaking. STAD technique implementation was found to be in the good category with a level of 86,21 percent, indicating that STAD technique had a positive effect on students' perspective. Based on the percentage of all instrument answer choices on the criterion, it was discovered that 55.5 percent of students indicated strongly agree (SA) and 40 percent stated agreeing (A) Keywords: STAD Technique, Speaking Skill